A review on hybrid photovoltaic – Battery energy storage system: Current status, challenges, and future directions. (July 2022) - Rana, Md Masud; Uddin, Moslem; Sarkar, Md Rasel; Shafiullah, G.M.; Mo, Huadong; Atef, Mohamed
Abstract: Currently, Photovoltaic (PV) generation systems and battery energy storage systems (BESS) encourage interest globally due to the shortage of fossil fuels and environmental concerns. PV is pivotal electrical equipment for sustainable power systems because it can produce clean and environment-friendly energy directly from the sunlight. On the other hand, cost-effectiveness, adequate performance, prompt response time, prominent lifecycle etc., heighten the attractiveness of BESS. This review paper presents comprehensive and significant research conducted on the state-of-the-art of hybrid PV-BESS system. The research studies conducted with hybrid PV-BESS system is also critically reviewed in this study, highlighting their strengths, weaknesses, barriers/limitations, and future opportunities for improvement. This study explored six different areas where the hybrid PV-BESS system is analyzed: lifetime improvement, cost reduction analysis, optimal sizing, mitigating various power quality issues, optimal control of power system, and peak load shifting and minimizing. The existing research conducted with a hybrid PV-BESS system is considered in this review study to find out its potentiality for power system application as well as to improve its further operations. A simulation case study has also been undertaken to evaluate the potentiality of an existing peak shaving strategy. Finally, insights into future directions are provided for further advancement of hybrid PV-BESS systems. Highlights: A brief overview of various microgrids, PV and BESS systems with their critical information is presented. Existing research on hybrid PV-BESS systems is extensively elaborated with their strengths and weaknesses. A simulation case study with an existing peak shaving strategy is conducted to evaluate the performance. Observed challenges with possible mitigation strategies are discussed briefly. Possible future directions and recommendations of the research on hybrid PV-BESS systems are presented.